Design and Optimization of a Rack and Pinion Type WEC Using an Auxiliary Vibrating System - Avikash Kaushik Chand; Farid Mahboubi Nasrekani; Kabir Mamun; Sumesh Narayan (Center of Biomass & Renewable Energy, Diponegoro University, 2023)
Research on wave energy converters with Rack and pinion type Power Take-Off (PTO) has been increasing over the last few years. A few control methods are used to optimize the performance of the said Wave Energy Converters (WECs). This paper presents a novel auxiliary vibrating system that can be implemented to improve the power input to a wave energy converter with a rack and pinion type PTO in regular waves. The design of the WEC system includes a floater, a double rack and pinion arrangement, a vibrating system, and a Mechanical Motion Rectifier (MMR) consisting of two one-way bearings that can convert the bidirectional wave motion to a unidirectional rotation of the output shaft. Once the waves move the floater upwards, this compresses the vibrating system which absorbs some of the energy and then the vibrating system helps the floater return to its original position by releasing the stored energy. The vibrating system also serves as a control method for limiting rack movement, so the impact of the waves is not detrimental to the system. This article aims to approximate the optimized power input to the system and investigate whether the implementation of a novel vibrating system improves the system power input. Allowing the WEC’s natural frequency to reach the wave’s natural frequency is important as it allows for maximum power absorption. The use of vibration systems to tune the WEC’s natural frequency close to the waves’ is novel and serves as the main factor in choosing this research. The WEC was modeled as 2 spring mass damper systems. Then the characteristic equations of the systems were extracted from the equations of motion and solved analytically to obtain the responses. One-factor-at-a-time (OFAT) method together with two different algorithms (Genetic and Multi-Start algorithms) from MATLAB code were used to optimize the response. The optimized power input to the system was then approximated. For system one, the maximum amplitude of the response was seen at a system mass of 500 kg and stiffness in the range of 100<k<240 N/m. The same was achieved for system two at a system mass of 500 kg and stiffness in the range of 100<k<138. The effect of the stiffness and mass on the response and input power has also been discussed.